On the geometry on special spaces of hyperplane elemente - Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2007)
In this paper analystes metric space of hyperplane elemente with special metric. Is prowed, that in such spaces intrinsic almost complex and almost product structures exists, criteria of its integrability and associated connections established.
Keywords: space of hyperplae elemente; almost complex and almost product structures; integrable structures; associated connections